2020
DOI: 10.3390/catal10010051
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between the Pore Structure of Mesoporous Silica Supports and the Activity of Nickel Nanocatalysts in the CO2 Reforming of Methane

Abstract: The question remains over the role of the pore structure of the support material on the catalytic behaviour of Ni catalysts during the CO2/dry reforming of methane (DRM). For this reason, a series of mesoporous materials with different pore structures, namely MCM-41, KIT-6, tri-modal porous silica (TMS), SBA-15 and mesostructured cellular foams (MCFs) were synthesised via hydrothermal synthesis methods and further impregnated with 15 wt.% NiO (11.8 wt.% Ni). It was observed that synthesised TMS is a promising … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 91 publications
2
20
0
1
Order By: Relevance
“…The high activity of the fiber/GMB composite material may be due to the higher resident time of reactants at the catalyst surface or due to the more favorable energy state of the nanofiber surface. The activities found for the composite material are comparable to other silica-supported nickel-based catalysts in steam-reforming processes [10], and the conversion is also comparable to nickel nanoparticles with no support material [30]. These preliminary data suggest that a composite structure silica fibers and GMBs may function as a suitable support material for steam methane reformation and similar processes.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The high activity of the fiber/GMB composite material may be due to the higher resident time of reactants at the catalyst surface or due to the more favorable energy state of the nanofiber surface. The activities found for the composite material are comparable to other silica-supported nickel-based catalysts in steam-reforming processes [10], and the conversion is also comparable to nickel nanoparticles with no support material [30]. These preliminary data suggest that a composite structure silica fibers and GMBs may function as a suitable support material for steam methane reformation and similar processes.…”
Section: Discussionsupporting
confidence: 53%
“…Many processes that use nickel-based catalysts, such as methane reforming and CO 2 methanation, are hindered by sintering of the nickel particles at high temperatures [9]. Silica, specifically mesoporous SBA-15, has been shown to be a suitable support for nickel in these applications as dispersion of the nickel particles prevents sintering and allows for the preservation of a greater number of active sites [10][11][12][13][14]. As such, GMBs may have similar success as a support material for nickel and NiO.…”
Section: Introductionmentioning
confidence: 99%
“…Efficiency of the Ni-based catalysts in relation to various processes is widely discussed in the literature [ 39 ]. The porous structure of the support plays a tremendous role in both the activity and stability of the catalysts.…”
Section: Resultsmentioning
confidence: 99%
“…It can be concluded that the sol-gel technique provided the synthesis of a more efficient catalytic system, which yielded a higher relative amount of nanostructured carbon. Efficiency of the Ni-based catalysts in relation to various processes is widely discussed in the literature [39]. The porous structure of the support plays a tremendous role in both the activity and stability of the catalysts.…”
Section: Catalytic Chemical Vapor Deposition Of 12-dichloroethanementioning
confidence: 99%
“…Admittedly, on a mole for mole basis, Ni is about 10000 times cheaper than Pt and 200 times cheaper than Pd [34]. Therefore, from practical and industrial viewpoints, Ni-based catalysts are the most attractive and promising for DRM [2,35].…”
Section: Catalystsmentioning
confidence: 99%